Setting the record straight UN salaries and benefits. - United Nations. Department of Public Information (1997)
The United Nations has been criticized for the allegedly lavish salaries and benefits it gives its staff. Critics also assert that United Nations employees are exempt from taxes and that all enjoy such "perks" as home-rental subsidies, tuition grants and free parking. With UN reform and cost-cutting at the top of Secretary-General Kofi Annan's agenda, the question of United Nations salaries and benefits is being raised with increasing frequency.
Typescript.
Also available at http://www.un.org/News/facts/salaries.htm
Keywords: United Nations -- Officials and employees -- Salaries, etc; United Nations -- Finance